The Incidence and Nature of Employee Profit Sharing and Share Ownership in Canada - Long, Richard J. (Relations industrielles / Industrial Relations, 1992)
In recent years, both profit sharing and employee ownership have experienced a dramatic resurgence of interest in most western countries. As companies have attempted to find ways of dealing with difficult economic circumstances and increased global competition, they have become receptive to these concepts. However, both types of plans find opponents within the labor unions. A recent study describes the incidence and general nature of employee profit sharing and share ownership in Canada, based on telephone interviews with chief executive officers of 626 Canadian firms conducted during 1989 and 1990. The results indicate that there has been a dramatic growth in both of these during the past decade, despite the absence of strong legislative support, and that this growth will likely continue for some time.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Data collection; ESOP; Employees; Labor Unions; Profit sharing plans; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Statistical data; Stockholders; Trends